A comparison between the effects of Keller Plan and traditional teaching methods on structure of learning outcomes among tertiary mathematics students. - Freislich, Mary R. (Curtin University, 1997)
The goal of the present project was to evaluate a mastery learning teaching method in mathematics for engineering undergraduates. Many mathematics teachers are very dissatisfied with the level of understanding displayed by students who pass traditional examinations. The Keller Plan requires mastery demonstrated by almost perfect performance on a sequence of tests which students repeat until they reach the high standard required.The study compared students in the same mathematics subject in the year before a change to Keller Plan teaching, and in the year of the change. Achievement scores, defined in terms of the completeness and consistency of solutions to test problems on the whole of the syllabus, were higher for the Keller Plan group. Measures of attitudes and approaches to study, which were positively related to achievement, indicated that the Keller Plan group had stronger intrinsic motivation, and more diligent study methods. Their confidence tended to be lower than that of the traditionally taught group, but was not low in absolute, and appreciation of the greater challenge of the Keller Plan appeared to be worked out via diligence. Students felt that individual work in the Keller Plan was a better use of time than attending traditional lectures.